Role of deep brain stimulation therapy in the magnetic resonance-guided high-frequency focused ultrasound era: current situation and future prospects. (2nd January 2020) - Fernandez-Garcia, C.; Alonso-Frech, F.; Monje, M.H.G.; Matias-Guiu, J.
ABSTRACT: Introduction : Deep brain stimulation (DBS) is a well-established treatment of movement disorders; but recently there has been an increasing trend toward the ablative procedure magnetic resonance-guided focused ultrasound (MRgFU). DBS is an efficient neuromodulatory technique but associated with surgical complications. MRIgFUS is an incision-free method that allows thermal lesioning, with fewer surgical complications but irreversible effects. Areas covered : We look at current and prospective aspects of both techniques. In DBS, appropriate patient selection, improvement in surgical expertise, target accuracy (preoperative and intraoperative imaging), neurophysiological recordings, and novel segmented leads need to be considered. However, increased number of older patients with higher comorbidities and risk of DBS complications (mainly intracranial hemorrhage, but also infections, hardware complications) make them not eligible for surgery. With MRgFUS, hemorrhage risks are virtually nonexistent, infection or hardware malfunction are eliminated, while irreversible side effects can appear. Expert commentary : Comparison of the efficacy and risks associated with these techniques, in combination with a growing aged population in developed countries with higher comorbidities and a preference for less invasive treatments, necessitates a review of the indications for movement disorders and the most appropriate treatment modalities.